The classical dramatic text and its value in contemporary theatre - Žavbi Milojević, Nina (Journal of Education Culture and Society, 2020)
This paper deals with the classical dramatic text and its staging in contemporary theatre. Specifi cally, it aims to show that classical texts can address topical issues. This is illustrated by the example of several stagings of Ivan Cankar’s Hlapci, one of the most infl uential dramatic texts in Slovene literature. The history of this dramatic text is presented from its fi rst publication and reception to the different stagings in various Slovene professional theatres. The focus is on how the situation in Slovene society is refl ected in each examined staging. The drama Hlapci was fi rst staged almost one hundred years ago, when the staging followed closely the dramatic text. However, after 1980 stagings became more independent from the text and more artistic freedom was allowed. The paper will prove that classical dramatic texts are very appropriate for staging in contemporary theatre, especially with an innovative director’s approach.